2015
DOI: 10.1021/acsami.5b09861
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of TiOxCy as Catalyst Support for Direct Ethanol Fuel Cells at Intermediate Temperature: From Planar Systems to Powders

Abstract: To achieve complete oxidation of ethanol (EOR) to CO2, higher operating temperatures (often called intermediate-T, 150-200 °C) and appropriate catalysts are required. We examine here titanium oxycarbide (hereafter TiOxCy) as a possible alternative to standard carbon-based supports to enhance the stability of the catalyst/support assembly at intermediate-T. To test this material as electrocatalyst support, a systematic study of its behavior under electrochemical conditions was carried out. To have a clear descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 38 publications
3
42
0
Order By: Relevance
“…S6, the ultrathin NiAl-LDH-NSs have a good catalytic activity for acetaldehyde while have no catalytic performance for acetic acid, demonstrating the acetic acid is the final product in this reaction process. Combine the results in our work and the general reported EOR reaction mechanism by Ni-based catalysts in the literature [12,13], the EOR reaction process by ultrathin NiAl-LDH-NSs in this work is as follows: Ni(OH)2+OHNiOOH+H2O+e NiOOH+CH3CH2OHCH3CHO+Ni(OH)2 NiOOH+CH3CHOCH3COOH+Ni(OH)2…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…S6, the ultrathin NiAl-LDH-NSs have a good catalytic activity for acetaldehyde while have no catalytic performance for acetic acid, demonstrating the acetic acid is the final product in this reaction process. Combine the results in our work and the general reported EOR reaction mechanism by Ni-based catalysts in the literature [12,13], the EOR reaction process by ultrathin NiAl-LDH-NSs in this work is as follows: Ni(OH)2+OHNiOOH+H2O+e NiOOH+CH3CH2OHCH3CHO+Ni(OH)2 NiOOH+CH3CHOCH3COOH+Ni(OH)2…”
Section: Resultssupporting
confidence: 73%
“…However, high cost, low abundance and catalytic poisoning by the carbon monoxide produced in electrooxidation have severely restricted the practical usage of Pt-based electro-catalysts in direct ethanol fuel cells (DEFCs) [10,11]. To overcome these problems, a broad range of non-precious metal catalysts have been actively pursued including metal [12], metal oxides [13], hydroxides [14] and sulfides [15]. Recently, layered double hydroxides (LDHs) have been reported as a promising candidate for various electrocatalytic systems [1619] including EOR [18,19] owing to their novel structure and desirable properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The titanium substrate stabilizes the Ti−O−C film and provides the electrical contact, which is essential for electrochemical investigations. However, the optimal film composition with regard to interfacial electrical conductivity and catalytic performance of deposited Pt has not been identified yet ,,. TiO x C y films are prone to surface reoxidation (to TiO 2 ) when exposed to air or during anodic polarization, which is due to the intrinsic thermodynamic instability of the oxycarbide phase ,.…”
Section: Introductionmentioning
confidence: 99%
“…However, the optimal film composition with regard to interfacial electrical conductivity and catalytic performance of deposited Pt has not been identified yet ,,. TiO x C y films are prone to surface reoxidation (to TiO 2 ) when exposed to air or during anodic polarization, which is due to the intrinsic thermodynamic instability of the oxycarbide phase ,. Moreover, and interestingly for the development of (intermediate temperature) direct ethanol fuel cell electrodes, it was shown that the addition of ethanol inhibits anodic oxidation of TiO x C y .…”
Section: Introductionmentioning
confidence: 99%